Review of Reading Through Theory. Studies in Theory-Framed Interpretation of the Literary Text - Cristian, Réka M. (AMERICANA E-journal of American Studies in Hungary, 2021)
Reading Through Theory. Studies in Theory-Framed Interpretation of the Literary Text Enikő Bollobás Eötvös University Press, Budapest, 2021. 274 pages ISBN 978-963-489-297-7